AGAMA KATOLIK DI KOTA JAMBI 1925 – 2013 - Siti Heidi Karmela, Eva Meliana Magdalena Panggaribuan, (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2020)
AbstractThis research is a historical research with the theme of religion which examines religion from an empirical point of view rather than from a normative point of view. As for what is being researched is about the growth and development of Catholicism in the city of Jambi. Therefore, the purpose of this research is to explain historically the dynamics of Catholicism in Jambi City from the initial process of its spread to its development since the Dutch colonial period, the Japanese occupation, to independence, and to describe the existence of missionary groups who were important figures in the process of its spread. The method used is the historical method starting from the heuristic, criticism, interpretation, and historiographic stages. Some of the theories used refer to the theory from E.B. Taylor on the "theory of the soul" or "anima", Stephen K, Anderson on the "theory of stages of religious development", and the theory of R.N. Bellah on the evolution of religion. In the end, the findings obtained after conducting field research were that the Catholic religion that developed in Jambi City has gone through a long process in its history, was carried and spread by missionary groups (priests, brothers, nuns), and contributed a lot to the lives of the population starting from field work. religious, social, and economic.Keywords: Religion, Catholicism, Missionary, Jambi City AbstrakPenelitian ini merupakan penelitian sejarah yang bertemakan bertemakan agama yang mengkaji agama dari sudut empiris bukan dari segi normatifnya. Adapun yang diteliti adalah tentang pertumbuhan dan perkembangan agama Katolik di Kota Jambi. Oleh karenanya tujuan penelitian ini adalah menjelaskan secara historis dinamika agama katolik di Kota Jambi mulai dari proses awal penyebaran hingga perkembangannya  sejak periode Kolonial Belanda, Pendudukan Jepang, hingga kemerdekaan, serta mendeskripsikan keberadaan kelompok misionaris yang menjadi tokoh penting dalam proses penyebarannya. Metode yang digunakan adalah metode sejarah mulai dari tahapan heuristik, kritik, interpretasi, dan historiografi. Beberapa teori yang dipakai mengacu pada  Teori dari E.B. Taylor tentang “teori jiwa” atau “anima”, Stephen K, Anderson tentang “teori tahapan perkembangan agama”, dan teori dari R.N. Bellah tentang evolusi agama. Pada akhirnya hasil temuan yang didapat setelah melakukan penelitian lapangan adalah bahwa agama Katolik yang berkembang di Kota Jambi telah melewati proses panjang dalam sejarahnya, dibawa dan disebarkan oleh kelompok misionaris (pastor, bruder, suster), dan banyak berkontribusi bagi kehidupan penduduk mulai dari karya bidang keagamaan, sosial, dan ekonomi.Kata Kunci : Agama, Katolik, Misionaris, Kota Jambi